University students’ emotions about learning subjects through English as a medium of instruction - Galván Malagón, M. Carmen; Morera-Bañas, M. Isabel (Frontiers in education (Lausanne), 2025)
Learning academic subjects in English can evoke a range of emotions among university students. For some students, learning a new language represents a valuable opportunity to expand their perspectives and communicate with people from diverse cultural backgrounds. For others, the language barrier can be an obstacle to understanding and expressing themselves, which can lead to feelings of lack of confidence. In this study, we are interested in the emotions that students may experience when they are in class learning subjects through English Medium Instruction (EMI). For this purpose, an Achievement Emotions Questionnaire with Likert-type questions was used. It includes items about their degree of confidence, anxiety, motivation or emotions when learning through EMI. The sample consisted of 231 students in the bilingual Primary Education program and in the Foreign Languages Approach Program of the University of Extremadura (PALEx). The results show significant differences between men and women in the case of shame, emotion experienced more by women than by men. However, the average number of women who feel positive emotions such as hope, enjoyment and pride is higher than that of men although the fact that they are unable to meet their expectations leads them to suffer from anxiety or disappointment to a greater extent than men. Nevertheless, men present a higher average in the emotions of anger and boredom. The results also show that the self-perceived level of English is relevant for experiencing positive emotions: the higher the level, the more enjoyable the English classes are and the more hope for success.